2007
DOI: 10.1111/j.1471-4159.2007.04847.x
|View full text |Cite
|
Sign up to set email alerts
|

NMDA‐mediated release of glutamate and GABA in the subthalamic nucleus is mediated by dopamine: an in vivo microdialysis study in rats

Abstract: The present study investigated the effects of N-methyl-Daspartic acidAEH 2 O (NMDA) on the dopamine, glutamate and GABA release in the subthalamic nucleus (STN) by using in vivo microdialysis in rats. NMDA (100 lmol/L) perfused through the microdialysis probe evoked an increase in extracellular dopamine in the STN of the intact rat of about 170%. This coincided with significant increases in both extracellular glutamate (350%) and GABA (250%). The effect of NMDA perfusion on neurotransmitter release at the leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 76 publications
1
6
0
Order By: Relevance
“…In GABAergic cells, glutamate taken up by EAAT4 can serve as a precursor for neosynthesis of GABA (Furuta et al,1997; Seal and Amara,1999) and thus enhance the inhibitory synaptic strength. In addition, the presence of EAAT4 on striatal neurons might be part of the glutamatergic regulation of the dopaminergic activity in the striatum as well as the STN, described by Wüllner et al (1994) and Ampe et al (2007), respectively. Small fractions of ionotropic and metabotropic striatal EAA binding sites are located on dopaminergic terminals where they may have a distinct impact on dopaminergic activity.…”
Section: Discussionmentioning
confidence: 94%
“…In GABAergic cells, glutamate taken up by EAAT4 can serve as a precursor for neosynthesis of GABA (Furuta et al,1997; Seal and Amara,1999) and thus enhance the inhibitory synaptic strength. In addition, the presence of EAAT4 on striatal neurons might be part of the glutamatergic regulation of the dopaminergic activity in the striatum as well as the STN, described by Wüllner et al (1994) and Ampe et al (2007), respectively. Small fractions of ionotropic and metabotropic striatal EAA binding sites are located on dopaminergic terminals where they may have a distinct impact on dopaminergic activity.…”
Section: Discussionmentioning
confidence: 94%
“…In PD, disturbance of glutamate homeostasis and excitotoxicity are associated with excessive NMDAR activation ( Wang J. et al, 2020 ; Trudler et al, 2021 ) and insufficient glutamate reuptake in the striatum ( Calon et al, 2003 ; Iovino et al, 2020 ). In early PD, this glutamatergic hyperactivity may compensate for the loss of neurons in SN ( Ampe et al, 2007 ; Shimo and Wichmann, 2009 ), but as the disease progresses, it causes impairment of the striatal signaling loop. In addition, VGluT1 and VGluT2 levels are altered in specific regions of the Parkinson’s brain.…”
Section: Glutamatergic Systemmentioning
confidence: 99%
“…Several anatomical studies provided evidence for a direct and substantial nigrosubthalamic dopaminergic projection in rats (Campbell et al, 1985;Canteras et al, 1990;Hassani et al, 1996). Moreover, we and others have shown that dopamine is released within the STN in vivo (Cragg et al, 2004;Ampe et al, 2007). However, despite numerous investigations, many discrepancies still exist with regard to the effect of dopamine and its receptor agonists on the activity of STN neurons.…”
Section: Role Of Dopamine At the Level Of The Subthalamic Nucleusmentioning
confidence: 92%